Effective Runtime Resource Management Using Linux Control Groups with the BarbequeRTRM Framework - Bellasi, Patrick; Massari, Giuseppe; Fornaciari, William (ACM transactions on embedded computing systems, 2015)
The extremely high technology process reached by silicon manufacturing (smaller than 32nm) has led to production of computational platforms and SoC, featuring a considerable amount of resources. Whereas from one side such multi- and many-core platforms show growing performance capabilities, from the other side they are more and more affected by power, thermal, and reliability issues. Moreover, the increased computational capabilities allows congested usage scenarios with workloads subject to mixed and time-varying requirements. Effective usage of the resources should take into account both the application requirements and resources availability , with an arbiter, namely a resource manager in charge to solve the resource contention among demanding applications. Current operating systems (OS) have only a limited knowledge about application-specific behaviors and their time-varying requirements. Dedicated system interfaces to collect such inputs and forward them to the OS (e.g., its scheduler) are thus an interesting research area that aims at integrating the OS with an ad hoc resource manager. Such a component can exploit efficient low-level OS interfaces and mechanisms to extend its capabilities of controlling tasks and system resources. Because of the specific tasks and timings of a resource manager, this component can be easily and effectively developed as a user-space extension lying in between the OS and the controlled application. This article, which focuses on multicore Linux systems, shows a portable solution to enforce runtime resource management decisions based on the standard control groups framework. A burst and a mixed workload analysis, performed on a multicore-based NUMA platform, have reported some promising results both in terms of performance and power saving.